Engaging Farmers in Climate Change Adaptation Planning: Assessing Intercropping as a Means to Support Farm Adaptive Capacity - and Himanen, Sari J.; Mäkinen, Hanna; Rimhanen, Karoliina; Savikko, Riitta (Agriculture, 2016)
Agriculture is one of the most vulnerable and adaptation-prone sources of livelihood facing climate change. Joint adaptation planning by farmers and researchers can help develop practically feasible and environmentally and economically sound adaptation actions as well as encourage the proactive building of farm adaptive capacity. Here, the perceptions of Finnish farmers and rural stakeholders regarding intercropping, the cultivation of two or more crop genotypes together in time and space, as a means to prepare for climate change, were collected in an open workshop. Our aim was to identify the potentials and challenges associated with intercropping, its role as an adaptation strategy, and in farm adaptive capacity. Qualitative analysis revealed better yield security, increased nutrient and protein self-sufficiency, soil conservation and maintenance, reduced pathogen pressure and regulation of water dynamics as the main perceived potentials of intercropping. Potentials relating to the farm economy and environment were also recognized. The main challenges associated with intercropping were related to the lack of information on crop variety performance and optimal yielding in mixtures, industry and policy requirements for seed purity, more complicated crop management and harvesting, and the economic risks associated with experimenting with novel mixtures. Nitrogen-fixing legumes; deep-rooted species, such as lucerne (Medicago sativa L.); special crops, such as herbs in forage mixtures; and autumn-sown winter oilseeds and cereals were highlighted as the most promising intercrops. Because the recognized potentials relate to the safeguarding of field cropping from anticipated climate change and the associated weather variability, we conclude that intercropping can serve as one adaptation strategy to strengthen the adaptive capacity of Finnish farms. However, assuring markets and policies that allow the development of intercropping, performing experiments to assess the benefits and implement options in practice, and providing farmers and farm advisors with more knowledge on the method represent the critical prerequisites for the broader adoption of intercropping.
Keywords: Adaptation planning; Adaptive capacity; Climate change; ecological intensification; intercropping; yield security